Diagnosis of the primary infection by pneumocystis in autopsy specimens from two infants using lung impression smears (touch preps) - Carolina A. Ponce; Rebeca I. Bustamante; Myriam Gallo; Sergio L. Vargas (Medical Mycology Case Reports, 2014)
The primary infection by Pneumocystis of normal, healthy infants is asymptomatic and goes undiagnosed. Microscopy diagnosis of Pneumocystis was sought in lung impression smears (LIS) from two ~3-month-old infants dying unexpectedly in the community. Pneumocystis nuclei and cysts were identified using Hema-Gurr with subsequent Gomori–Grocott staining in the same spot documenting that these stains may be complementary. LIS provide for an observer–dependent, inexpensive, and ready-available method for detection of Pneumocystis in infant lungs.